Godkins' displeased response to letter from Snell - Correspondence: Godkins to Snell - Godkins, Thomas R. (1972)
Godkins communicates his belief to Snell that the American College of Physicians' Assistants has intentionally tried to deceive its members, saying "You must realize, however, that your letter has put the merger in a precarious position".